Role of caveolin-1 in the regulation of lipoprotein metabolism - Philippe G. Frank; Stephanos Pavlides; Michelle W.-C. Cheung; Kristin M. Daumer; Michael P. Lisanti (2008)
Lipoprotein metabolism plays an important role in the development of several human diseases, including coronary artery disease and the metabolic syndrome. A good comprehension of the factors that regulate the metabolism of the various lipoproteins is therefore key to better understanding the variables associated with the development of these diseases. Among the players identified are regulators such as caveolins and caveolae. Caveolae are small plasma membrane invaginations that are observed in terminally differentiated cells. Their most important protein marker, caveolin-1, has been shown to play a key role in the regulation of several cellular signaling pathways and in the regulation of plasma lipoprotein metabolism. In the present paper, we have examined the role of caveolin-1 in lipoprotein metabolism using caveolin-1-deficient (Cav-1(-/-)) mice. Our data show that, while Cav-1(-/-) mice show increased plasma triglyceride levels, they also display reduced hepatic very low-density lipoprotein (VLDL) secretion. Additionally, we also found that a caveolin-1 deficiency is associated with an increase in high-density lipoprotein (HDL), and these HDL particles are enriched in cholesteryl ester in Cav-1(-/-) mice when compared with HDL obtained from wild-type mice. Finally, our data suggest that a caveolin-1 deficiency prevents the transcytosis of LDL across endothelial cells, and therefore, that caveolin-1 may be implicated in the regulation of plasma LDL levels. Taken together, our studies suggest that caveolin-1 plays an important role in the regulation of lipoprotein metabolism by controlling their plasma levels as well as their lipid composition. Thus caveolin-1 may also play an important role in the development of atherosclerosis.